2018
DOI: 10.1002/adma.201802792
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Healing Micellar Ion Gels Based on Multiple Hydrogen Bonding

Abstract: Ion gels, composed of macromolecular networks filled by ionic liquids (ILs), are promising candidate soft solid electrolytes for use in wearable/flexible electronic devices. In this context, the introduction of a self-healing function would significantly improve the long-term durability of ion gels subject to mechanical loading. Nevertheless, compared to hydrogels and organogels, the self-healing of ion gels has barely investigated been because of there being insufficient understanding of the interactions betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
178
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(184 citation statements)
references
References 55 publications
5
178
1
Order By: Relevance
“…The quantitative self‐healing experiments were performed in water, and the mechanical tensile test showed a good healing efficiency (Figure E), in which the mechanical strength recovered 93.9 % of the original moduli and the breaking elongation fully recovered. The good self‐healing efficiency under water might be attributed to the presence of dynamic ionic bonds at the interfaces . To evaluate the water‐stability of the ionic‐cluster‐toughened network, soaking in water for several days led to no swelling or dissolution (Figure S22).…”
Section: Figurementioning
confidence: 99%
“…The quantitative self‐healing experiments were performed in water, and the mechanical tensile test showed a good healing efficiency (Figure E), in which the mechanical strength recovered 93.9 % of the original moduli and the breaking elongation fully recovered. The good self‐healing efficiency under water might be attributed to the presence of dynamic ionic bonds at the interfaces . To evaluate the water‐stability of the ionic‐cluster‐toughened network, soaking in water for several days led to no swelling or dissolution (Figure S22).…”
Section: Figurementioning
confidence: 99%
“…h) The relationship between healing time and fracture energy of hydrogel. f–h) Reproduced with permission . Copyright 2018, Wiley‐VCH Verlag GmbH & Co. KGaA.…”
Section: Self‐healing Methodsmentioning
confidence: 99%
“…Presently, the mechanically tough hydrogels with self‐healing property based on hydrogen bonds have been paid considerable attention. In a more recent study, a new ion gel, which composed of the diblock copolymer and hydrophobic ionic liquid (IL), was prepared . By applying the multiple hydrogen bonding interactions of coronal chains in the IL surface, the ion gel successfully achieved self‐healing without the external intervene.…”
Section: Self‐healing Methodsmentioning
confidence: 99%
“…b) Schematic illustration and structures of self‐healing micellar ion gel. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Self‐healable Ionic Tactile Sensorsmentioning
confidence: 99%
“…Recently, Tamate et al demonstrated a new class of micellar ion gels composed of diblock copolymers with an IL‐phobic and a hydrogen‐bonding block with hydrogen bonds donating and accepting units (Figure b) . The diblock copolymer consisted of an IL‐phobic poly(styrene) (PS) block and a hydrogen bonding block composed of statistical copolymers of N,N ‐dimethylacrylamide (DMAAm) and acrylic acid (AAc) (i.e., PS‐ b ‐P(DMAAm‐r‐AAc)).…”
Section: Self‐healable Ionic Tactile Sensorsmentioning
confidence: 99%